Aksesibilitas Komunikasi Antar Pulau Di Desa Ameth Kecamatan Teon Nila Serua Kabupaten Maluku Tengah - Aulele, Philips; Rumra, Fatmawati (Jurnal Ilmu Komunikasi Pattimura, 2023)
Communication is very important for humans, especially the people of Ameth Viliage. Therefore, this study aims to analyze the inter-island communication process in Ameth Village ang analyze alternative government solutions to realize inter-island communication accessibillity services for the just people of Ameth Village. The formulation of the problem in this study includes how the accessibility of communication on Nila Island, Ameth Village can be used to meet information needs in people`s lives. This type of research is qualitative. Informants of this research amounted to 6 people. The determination of the informants was taken by purposive sampling, which is based on certain criteria as follows: the people of Ameth Village who are involved in the inter-island communication process, are male and female and aged 20-65 years. Data collection techniques used in this study were interviews, observation, and documentation. The results of this study indicate that inter-island communication carried out by the Ameth Village community is very important so that the community really needs the role of the government in helping to meethe information needs of the community in the inter-island communication process. It can be concluded that the communication carried out by the community has been very helpful, but there are several obstacles in the form of the use of communication media and the role of the government so that the government's role is needed in overcoming these obstacles.